Cover Image, Volume 39, Issue 9. Issue 9 (9th February 2018) - Unknown
Abstract : The image shows the spatial resolution of the zz component of the Nucleus Independent Chemical Shift (NICSzz) for two different probe points for benzene. NICSzz is commonly used as a quantifier of (anti)aromaticity. A NICSzz value is only a single scalar value and as a consequence, the interpretation of the value in terms of the underlying current density patterns is not straightforward. A detailed analysis of a NICSzz value is feasible by its resolution in space and sign. The cover image visualizes the spatial resolution for two different NICSzz probe points, one in the center of the molecule and one above the center of the molecule. On page 511, Patrick Bultinck and colleagues demonstrate the use of the resolutions in space, sign and orbitals in the interpretation of single scalar NICSzz values. (DOI:10.1002/jcc.25095 )